Perilla frutescens seed meal as a fat substitute mitigates heterocyclic amine formation and protein oxidation and improves fatty acid profile of pan-fried chicken patties - Khan, Iftikhar Ali; Shi, Baoping; Shi, Haibo; Nawaz, Asad; Zhu, Zongshuai; Ijaz, Muhammad Umair; Hussain, Muzahir; Khan, Asad; Wang, Mingfu; Chen, Feng; Wang, Daoying; Cheng, Ka-Wing (Frontiers in Nutrition, 2022)
Fatty acid profile, protein and fatty acid oxidation and flavor profile of pan-fried chicken patties formulated with various levels of Perilla frutescens seed meal (PSM) as a fat substitute was investigated in this study. The formation of heterocyclic amines (HCAs) in the chicken patties was also evaluated. The results showed that pan-fried patties formulated with 20% PSM (PSM4) had the highest ranges of oleic acid and ∑MUFA content and ∑PUFA/∑SFA ratio. Low to medium levels of PSM (PSM1, 2, and 3 corresponding to 5%, 10%, and 15% of PSM, respectively) reduced the content of lipid peroxidation products, while high level (PSM4) increased it. All levels of PSM were also found to be effective against elevation in carbonyl content relative to the control. Moreover, the PSM effectively inhibited HCA formation in the chicken patties. The total contents of HCAs in PSM1, PSM2, PSM3 and PSM4 samples were significantly (P<0.05) lower than that of the control sample, corresponding to 31.9%, 46.1%, 57.2%, and 44.8% inhibition, respectively. PSM4, however, had no or very little effect on the formation of PhIP, 4,8-DiMeIQx and AαC, despite a strong inhibitory effect on MeIQx formation. These findings not only support the promising potential of PSM for application as a fat substitute to improve the fatty acid profile and reduce the content of harmful by-products in heat-processed chicken, but also highlight that appropriate addition level is a critical factor in optimizing the functional capacity of this natural agent.